LITERATURE REVIEW : ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Septiani, Freliana; Fuadiyah, Sa’diatul (Universitas Cokroaminoto Palopo, 2025)
Critical thinking skills are one of the essential competencies of the 21st century that students must possess to face the challenges of the times. This study aims to analyze the level of students' critical thinking skills through a literature review of five relevant articles across different educational levels. The method used is a literature review with purposive sampling, where articles are selected based on the alignment of themes and pre-determined criteria. The analysis results show that, in general, students' critical thinking skills are still in the low to moderate category. Contributing factors include difficulties in understanding questions, lack of HOTS-based exercises, the influence of the learning environment, and limited habits of analyzing information. Therefore, joint efforts from teachers, schools, and students are required to enhance these skills through active, innovative, and problem-solving-based learning.